Making the Invisible Visible: Personas and Mental Models of Distance Education Library Users - Lewis, Cynthia; Contrino, Jacline (Journal of library & information services in distance learning)
Gaps between users' and designers' mental models of digital libraries often result in adverse user experiences. This article details an exploratory user research study at a large, predominantly online university serving non-traditional distance education students with the goal of understanding these gaps. Using qualitative data, librarians created personas and mental models focused on users' perceptions and obstacles in using a digital library and conducting research. The findings provided insight into the research habits and challenges of library users, thus allowing the library to make evidence-based decisions about designing digital learning objects and the library website.